HIF-1-Dependent Reprogramming of Glucose Metabolic Pathway of Cancer Cells and Its Therapeutic Significance - Nagao, Ayako; Kobayashi, Minoru; Koyasu, Sho; Chow, Christalle C. T.; Harada, Hiroshi (International journal of molecular sciences, 2019)
Normal cells produce adenosine 5′-triphosphate (ATP) mainly through mitochondrial oxidative phosphorylation (OXPHOS) when oxygen is available. Most cancer cells, on the other hand, are known to produce energy predominantly through accelerated glycolysis, followed by lactic acid fermentation even under normoxic conditions. This metabolic phenomenon, known as aerobic glycolysis or the Warburg effect, is less efficient compared with OXPHOS, from the viewpoint of the amount of ATP produced from one molecule of glucose. However, it and its accompanying pathway, the pentose phosphate pathway (PPP), have been reported to provide advantages for cancer cells by producing various metabolites essential for proliferation, malignant progression, and chemo/radioresistance. Here, focusing on a master transcriptional regulator of adaptive responses to hypoxia, the hypoxia-inducible factor 1 (HIF-1), we review the accumulated knowledge on the molecular basis and functions of the Warburg effect and its accompanying pathways. In addition, we summarize our own findings revealing that a novel HIF-1-activating factor enhances the antioxidant capacity and resultant radioresistance of cancer cells though reprogramming of the glucose metabolic pathway.